Contested childhoods: law and social deviance in wartime China, 1937-1945 - Chang, L (2011)
“Contested Childhoods” links together three major areas of historical inquiry: war and criminality, law and social change, and the law as it relates to children, in the first half of twentieth-century China. The founding of the People’s Republic of China (PRC) in 1949 has eclipsed the historical significance of Chiang Kai-shek’s Nationalist Government and the importance of its role during the wartime period. This study examines how the outbreak of China’s War of Resistance against Japan (1937-1945) served as a crucial catalyst to the construction of ideas of criminality and its relation to children during the wartime period. It examines the different measures by which Chiang Kai-shek’s Nationalist Government (1928-1949) attempted to handle the rise in levels of criminality involving juveniles. The study analyses how an increase in criminality during the wartime period challenged how ideas on and about children and childhood were in understood within Chinese society. Moreover, it argues that wartime conditions served as a crucial catalyst prompted the construction of a new judicial and legal framework that was aimed at delineating the boundaries between childhood and adulthood during this period.